2021
DOI: 10.3390/su13137329
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Tracking SDG Indicator Metrics with Gridded Population Data

Abstract: Achieving the seventeen United Nations Sustainable Development Goals (SDGs) requires accurate, consistent, and accessible population data. Yet many low- and middle-income countries lack reliable or recent census data at the sufficiently fine spatial scales needed to monitor SDG progress. While the increasing abundance of Earth observation-derived gridded population products provides analysis-ready population estimates, end users lack clear use criteria to track SDGs indicators. In fact, recent comparisons of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…This analysis reinforces findings of other studies which find that currently available gridded population products tend to underestimate populations in urban areas [ 94 96 ], especially in higher-density poorer neighbourhoods [ 97 ]. For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This analysis reinforces findings of other studies which find that currently available gridded population products tend to underestimate populations in urban areas [ 94 96 ], especially in higher-density poorer neighbourhoods [ 97 ]. For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region. Furthermore, they found that WorldPop-Global-Unconstrained generally performed better than un-modelled products (e.g., GPW), but not as well as products that constrained estimates to settled cells (e.g., GHS-POP) [ 94 ]. In a separate comparison of nine gridded population estimates of Kenyan and Nigerian slum populations (SDG 11.1.1) where field counts were available for reference, the estimated population in each slum varied widely and WorldPop-Global-Unconstrained estimates reflected just 11% of the overall slum population while the best performing data product (HRSL) estimated just 34% of all slum dwellers [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis reinforces findings of other studies which find that currently available gridded population products tend to underestimate populations in urban areas [94][95][96], especially in higher-density poorer neighbourhoods [97]. For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region.…”
Section: Plos Onesupporting
confidence: 90%
“…The potential uncertainty due to regional exposure data has not been thoroughly studied. There are a few exceptions for flood modeling, including: Englehardt et al (2019), which examines the effect that refined estimates of building exposure have on flood loss estimates based on the assignment of vulnerability and its sensitivity to the designation of ''urban'' and ''rural'' in developing countries, and an examination of using various global population data sets, as with Lim et al (2019) and Tuholske et al (2021).…”
Section: Introductionmentioning
confidence: 99%